Elaboration and Characterization of Bricks Made with Addition of Calcined Rice Husk (2021)
The growing demand for construction materials, the search for sustainable and environmentally friendly alternatives, and the new vision towards a circular economy have led to the increasing use of agricultural waste to obtain new value-added materials. The present research sought to elaborate and characterize bricks manufactured with addition of different concentrations of rice husk ash (5%, 10% and 15%). The average content of silicon oxide (SiO2) obtained in the rice husk ash was determined by gravimetry and then the bricks were manufactured according to the established concentrations. The bricks obtained were evaluated by means of compression, absorption, and warpage tests according to the parameters established in the NTP-399.61 for concrete bricks. The results showed that the average content of SiO2 in the rice husk ash was 79.08%. Likewise, in the compression and absorption tests it was observed that the ash concentration influenced the compressive strength and the percentage of water absorption, showing in the first test that the Tto (5%) was statistically similar (p<0.05) to the control with 24.6 MPa. Furthermore, the second test showed the lowest value compared to the control with 5.24% of water absorption. In conclusion, we can say that the substitution of 5% rice husk ash showed potential to produce cement bricks according to the parameters established in the NTP-399.601.